"One People, One Struggle": Anya-Nya propaganda and the Israeli Mossad in Southern Sudan, 1969–1971. Issue 3 (3rd July 2018) - Gidron, Yotam
ABSTRACT: This paper explores the involvement of the Mossad, Israel's national intelligence agency, in producing propaganda materials on behalf of the Southern Sudanese rebel group Anya-Nya, between 1969 and 1971. From 1961, Southern Sudanese politicians appealed for Israeli assistance in their struggle against the Sudanese government. Israelis saw great potential for anti-Arab propaganda in the Southern cause, but did not extend any significant support to the rebels until 1969. When they eventually did, they also embarked on a secret propaganda campaign on behalf of the Anya-Nya, seeking to promote the Southern struggle globally in order to delegitimize Arab nations and their Soviet supporters and draw attention away from anti-Israeli and pro-Palestinian propaganda in the aftermath of the Six-Day War of 1967. Unlike earlier Southern Sudanese publications, the Israeli materials made extensive use of photographs and projected a new image of the Southern Sudanese leadership and its relationship with civilians. The publications, the paper argues, advanced both Israeli and Southern Sudanese interests, and reflected both Southern Sudanese and Israeli notions of nation-building.